BEST PROSTHESIS FOR UNICOMPARTMENTAL KNEE ARTHROSIS: FIXED OR MOBILE? - Fabrício Luz Cardoso; Deusimar Cristian dos Santos Gomez; Fabrício Roberto Severino; Patrícia Maria Moraes de Barros de Fucs (Acta Ortopédica Brasileira, 2025)
Abstract This study aimed to compare fixed-bearing and mobile-bearing knee unicompartmental arthroplasty implants in adults (in the medial compartment) to determine which is better for each patient and their particularities. The research focused on postoperative assessments with a follow-up of at least a 2-year, examining both quality of life and mid-term functionality in the medium term. A systematic keyword search was executed in the PubMed, EMBASE, and Cochrane databases, employing a filter for randomized clinical trials and without language limitations. The search yielded 113 articles from March 28, 2024, including 83 from PubMed, 12 from EMBASE, and 18 from the Cochrane Library. The study found insufficient evidence to establish the superiority of one prosthetic type over the other regarding post-operative function, pain, complications, revisions, and quality of life after a 2-year follow-up. Literature highlights uncertainties in comparing UKA types due to varied assessment tools. No conclusive evidence favors either type regarding post-op function, pain, complication rates, revisions, or quality of life after 2 years. Urgent need for standardized, long-term, multicenter studies to inform evidence-based clinical practice. Level of Evidence I; Systematic review of randomized controlled trials.